ASSESSMENT OF CO2 EMISSION DUE TO SPEED BUMPS ON SELECTED HIGHWAYS IN BAUCHI STATE (FUDMA JOURNAL OF SCIENCES, 2024)
One industry that will emit carbon dioxide (CO2) that is dependent on the production of fossil fuels is transportation. Even though cars emit carbon dioxide (CO2), which contributes to air pollution, fossil fuel-powered vehicles nevertheless require widespread use. Traffic-calming devices act as tools to reduce the rapidity of automobiles. They make a major contribution to road protection; however, air contamination is more likely to arise due to the fact that motor vehicles use brakes and accelerate more regularly. This study examines the impact of speed bumps brought on by elevated carbon dioxide (CO2) levels on selected commercial vehicles, including Vectra, Volkswagon, Peugeot, Ford Galaxy, and Toyota Hiace buses, traveling on highways from Bauchi to Jos, Bauchi to Azare, Bauchi to Gombe, and Bauchi to Kano. To estimate the CO2 emissions of each kind of specified commercial vehicle, the fuel consumption of the vehicles before and after the installation of bumps was gathered using a questionnaire model and examined using a mathematical model using a macro-scale approach. The result shows that there is an increase of 21% in CO2 emissions on the Bauchi to Jos Highway, 15% in CO2 emissions on Bauchi to Azare, 24% in CO2 emissions on Bauchi to Gombe, and 40% in CO2 emissions on Bauchi to Kano. The study concludes that transport-related pollution on Bauchi Highway has indeed significantly increased with the installation of calming traffic devices, which is dangerous to human health and vegetation near these highways.
Keywords: Fossil fuel; Carbon dioxide (CO2); Emissions; Traffic-calming; Vehicles; Highways